End‐exercise ΔHHb/ΔVO2 and post‐exercise local oxygen availability in relation to exercise intensity. (17th November 2015) - Stöcker, F.; Von Oldershausen, C.; Paternoster, F. K.; Schulz, T.; Oberhoffer, R.
Summary: Increased local blood supply is thought to be one of the mechanisms underlying oxidative adaptations to interval training regimes. The relationship of exercise intensity with local blood supply and oxygen availability has not been sufficiently evaluated yet. The aim of this study was to examine the effect of six different intensities (40–90% peak oxygen uptake, VO2peak ) on relative changes in oxygenated, deoxygenated and total haemoglobin (ΔO2 Hb, ΔHHb, ΔTHb) concentration after exercise as well as end‐exercise ΔHHb/ΔVO2 as a marker for microvascular O2 distribution. Seventeen male subjects performed an experimental protocol consisting of 3 min cycling bouts at each exercise intensity in randomized order, separated by 5 min rests. ΔO2 Hb and ΔHHb were monitored with near‐infrared spectroscopy of the vastus lateralis muscle, and VO2 was assessed. ΔHHb/ΔVO2 increased significantly from 40% to 60% VO2 peak and decreased from 60% to 90% VO2 peak. Post‐exercise ΔTHb and ΔO2 Hb showed an overshoot in relation to pre‐exercise values, which was equal after 40–60% VO2peak and rose significantly thereafter. A plateau was reached following exercise at ≥80% VO2peak . The results suggest that there is an increasing mismatch of local O2 delivery and utilization during exercise up to 60% VO2peak . This insufficient local O2 distribution is progressively improved above that intensity. Further, exercise intensities of ≥80% VO2peak induce highest local post‐exercise O2 availability. These effects are likely due to improved microvascular perfusion by enhanced vasodilation, which could be mediated by higher lactate production and the accompanying acidosis.